me ajude por favor 13 pontos
Anexos:
![](https://pt-static.z-dn.net/files/dc4/0c7c6ac510f94419d95e14c0fdb73f09.jpg)
Soluções para a tarefa
Respondido por
1
(ab - c)² = a²b² - 2abc + c²
(a³ - b³) · (a³ + b³) ⇒ (a³)² - (b³)² =![a^6 - b^6 a^6 - b^6](https://tex.z-dn.net/?f=a%5E6+-+b%5E6)
⇒ x² - xy + (y/2)²
(a³ - b³) · (a³ + b³) ⇒ (a³)² - (b³)² =
Perguntas interessantes
Contabilidade,
11 meses atrás
História,
11 meses atrás
Inglês,
11 meses atrás
Português,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás